Respostas
respondido por:
2
a1 = 4
r = 3
===
a2 = a1 + r
a2 = 4 + 3
a2 = 7
a3 = a2 + r
a3 = 7 + 3
a3 = 10
a4 = a3 + r
a4 = 10 + 3
a4 = 13
PA = (4, 7, 10, 13)
===
===
Ou deste modo para encontrar os valores
an = a1 + ( n -1 ) . r
a2 = 4 + ( 2 -1 ) . 3
a2 = 4 + 1 . 3
a2 = 4 + 3
a2 = 7
===
an = a1 + ( n -1 ) . r
a3 = 4 + ( 3 -1 ) . 3
a3 = 4 + 2 . 3
a3 = 4 + 6
a3 = 10
===
an = a1 + ( n -1 ) . r
a4 = 4 + ( 4 -1 ) . 3
a4 = 4 + 3 . 3
a4 = 4 + 9
a4 = 13
PA = (4, 7, 10, 13)
r = 3
===
a2 = a1 + r
a2 = 4 + 3
a2 = 7
a3 = a2 + r
a3 = 7 + 3
a3 = 10
a4 = a3 + r
a4 = 10 + 3
a4 = 13
PA = (4, 7, 10, 13)
===
===
Ou deste modo para encontrar os valores
an = a1 + ( n -1 ) . r
a2 = 4 + ( 2 -1 ) . 3
a2 = 4 + 1 . 3
a2 = 4 + 3
a2 = 7
===
an = a1 + ( n -1 ) . r
a3 = 4 + ( 3 -1 ) . 3
a3 = 4 + 2 . 3
a3 = 4 + 6
a3 = 10
===
an = a1 + ( n -1 ) . r
a4 = 4 + ( 4 -1 ) . 3
a4 = 4 + 3 . 3
a4 = 4 + 9
a4 = 13
PA = (4, 7, 10, 13)
Helvio:
De nada.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás